FORMULASI DAN UJI STABILITAS FISIK SERUM WAJAH EKSTRAK KROKOT (Portulaca oleracea Linn) - Nia Yuniarsih; Amalia Haryani (Jurnal Buana Farma, 2022)
Purslane (Portulaca Oleracea L.) is a plant that contains natural antioxidants. Purslane has the highest concentration of omega-3 fatty acids, which is 30,000 ppm. Cosmetic serum is a skin treatment with a high concentration of active ingredients in its formula to provide intensive nutrition to the skin layers. Serum itself can be processed using two bases, namely water and oil bases. The purpose of this study was to determine the 96% purslane (P. Oleracea L.) Ethanol Extract could be formulated into a facial serum preparation and continued with evaluation of the physical stability of the purslane extract (P. Oleracea L.) facial serum. In this study using the Stability Test Method accelerated with several temperatures, including room temperature (27-29⁰C), temperature under sunlight, oven temperature 40⁰C. The results of testing the stability of serum preparations are organoleptic tests (typically aromatic odor, brownish white in color and in the form of serum gel) organoleptic results are stable, there is no change, homogeneity, pH value of 4.6-6, average value of Viscosity 1940-1998 Cp, and accelerated stability for 3 months. The results of this study obtained purslane serum with three different concentrations, namely 1%, 1.5%, and 2%, in the organoleptic stability test at room temperature, sun and a stable temperature of 40⁰C. However, the pH test and viscosity test stated that the purslane extract serum preparation was unstable in storage at room temperature, sun and 40⁰C due to a decrease in storage time.